Activists against research: Experiences studying wind energy in Ontario. (8th March 2018) - Walker, Chad; Christidis, Tanya
Abstract : Whether because instances are rare or because academics are uncomfortable writing about them, descriptions of activism against academic research cannot be easily found within the existing literature. In this paper, we share our experience of being young geographic researchers faced with impassioned opposition against our work. Studies we conducted of wind energy development in rural Ontario spurred backlash; activists used several means of opposing our research and attempted to discredit us as capable academics. We share examples of direct and indirect communication from such people and advise that there is much to be learned, especially for those who may not have the benefit of mentors intimately familiar with the type of activism we encountered. The paper closes with a practical discussion of three lessons written particularly for academics who may be entering similar areas of contested geographic research for the first time. Key Messages: We present a unique example of research participants and others as activists in a contested area of geographical research. Activists used several means to discredit our studies including threats and personal attacks. The paper closes with some advice for those entering or within similar areas of geographic or social scientific inquiry.